2012
DOI: 10.1039/c1jm14862a
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of diazonium functionalized graphene: A potential approach to change graphene electronic structure

Abstract: Graphene sheets were successfully functionalized with 4-nitrophenyl diazonium (NPD). Two dimensional Raman analysis demonstrated that the reaction preferred to happen on single-layer graphene rather than bi-layer or multi-layer, and the edges of graphene were more reactive than the central areas. Atomic force microscopy (AFM) indicated the aryl groups were covalently bonded to one side of the graphene basal plane in a perpendicular configuration. Transmission electron microscopy (TEM) and selected area electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 27 publications
1
44
1
Order By: Relevance
“…Graphene, a two-dimensional sheet of sp 2 hybridized carbon atoms packaged into a honeycomb lattice structure, is characterized by a large surface area, high mechanicalflexibility, excellent chemical stability [5,9], high mobility of electrons that experimentally calculated value was 1.5 × 10 8 m 2 /Vs at room temperature and very low resistivity (1 × 10 −4 Ωm) [10]. Thus, it is considered an important material for electroanalysis.…”
Section: Introductionmentioning
confidence: 96%
“…Graphene, a two-dimensional sheet of sp 2 hybridized carbon atoms packaged into a honeycomb lattice structure, is characterized by a large surface area, high mechanicalflexibility, excellent chemical stability [5,9], high mobility of electrons that experimentally calculated value was 1.5 × 10 8 m 2 /Vs at room temperature and very low resistivity (1 × 10 −4 Ωm) [10]. Thus, it is considered an important material for electroanalysis.…”
Section: Introductionmentioning
confidence: 96%
“…[31][32][33][34][35][36][37][38][39][40][41] For example, NPD functionalized graphene exhibits field-controlled magnetic behavior. 42,43 A recent experiment demonstrated that the NPD modification of graphene can be spatially controllable, 40 which makes the NPD functionalization technique particularly useful for tailor-made twodimensional material design.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported to detect furazolidone, including HPLC [8], LC-MS [9], LC-MS/MS [10], ELISA [11], spectrophotometry [12] and fluorimetry [13,14]. However, most of several unique properties such as excellent electronic conductivity, high specific surface area, high mechanical-flexibility [27], high charge mobility and thermal conductivity [28,29]. Therefore, it has stimulated interest in applications for graphene-based nanocomposites including photovoltaics, phtocatalysis, nanoelectronics, and sensors [29].…”
Section: Introductionmentioning
confidence: 99%